On Frank Ruda, Hegel’s Rabble: An Investigation into Hegel’s Philosophy of Right - Rosendal, Søren (Stasis, 2016)
Book review: Frank Ruda, Hegel’s Rabble: An Investigation into Hegel’s Philosophy of Right